السياسة الألمانية تجاه البلدان المغاربية (الجزائر , تونس , المغرب ) خلال الحرب العالمية الأولى 1914_1918 - آية بن دبيلي; ليندة بحيري (جامعة الوادي - University of Eloued, 2025)
"الملخص : مع اندلاع الحرب العالمية الأولى سنة 1914م ، دخل العالم مرحلة جديدة من الصراع الدولي، انعكست تداعياته على مختلف المناطق، بما في ذلك دول المغرب العربي التي كانت آنذاك تحت السيطرة الاستعمارية الفرنسية ، حيث سعت ألمانيا إلى توسيع نفوذها السياسي والدعائي خارج أوروبا، مستهدفة مناطق النفوذ الفرنسي والبريطاني، وعلى رأسها دول المغرب العربي ، واعتمدت في هذا الإطار على استخدام وسائل وأساليب عديدة لكسب تأييد الشعوب المغاربية، وركزت بشكل خاص على البعد الديني والقومي لاستمالتهم وتحريضهم ضد الوجود الفرنسي وذلك من خلال تصوير ألمانيا کحليف للمسلمين ومعادٍ للاستعمار الفرنسي، مستغلة مشاعر الرفض المحلي للاحتلال، كما حاولت التأثير على المجندين المغاربة في صفوف الجيش الفرنسي، وتشجيع التمرد والانشقاق داخل المستعمرات. غير أن السلطات الفرنسية أدركت خطورة هذه التحركات، فبادرت إلى الرد بسياسات مضادة شملت تشديد الرقابة، وتوظيف الخطاب الديني والوطني لترسيخ شرعية وجودها، وهذا ما أدى إلى فشل كل المحاولات الألمانية في تحقيق أهدافها في المنطقة وتراجع مكانتها الدولية مع نهاية الحرب العالمية الأولى عام 1918م ، مع بقاء السيطرة والهيمنة الفرنسية على المنطقة. "Abstract: With the outbreak of World War I in 1914, the world entered a new phase of international conflict, the repercussions of which extended to various regions, including the Maghreb countries, which were at the time under French colonial rule. Germany sought to expand its political and propaganda influence beyond Europe, targeting areas under French and British control, particularly the Maghreb. In this context, it employed various means and methods to gain the support of the Maghrebi peoples, focusing especially on religious and nationalistic sentiments to sway them and incite them against the French presence. Germany portrayed itself as an ally of Muslims and an opponent of French colonialism, taking advantage of local resentment toward occupation. It also attempted to influence Moroccan soldiers serving in the French army and encouraged rebellion and division within the colonies. However, the French authorities recognized the seriousness of these moves and responded with countermeasures that included stricter surveillance and the use of religious and national discourse to reinforce the legitimacy of their presence. These efforts led to the failure of all German attempts to achieve their objectives in the region, and by the end of World War I in 1918, Germany's international standing had declined, while French control and dominance over the region remained intact. "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: الدعاية المضادة الفرنسية; الحرب العالمية الأولى; الدول المغاربية; الدعاية الألمانية; السياسة الألمانية; German policy; German propaganda; Maghreb countries; World War I; French counter-propaganda